Determinant factors affecting the improvement of education index - Jalil Setiawan Jamal; Muslim Salam; A. Nixia Tenriawaru; Didi Rukmana; Muhammad Hatta Jamil; Saadah Saadah (Graduate School, Universitas Negeri Yogyakarta, 2021)
The Human Development Index (HDI) of the Selayar Islands Regency experienced an insignificant improvement. The low education index causes the low HDI achievement of the Selayar Islands Regency because the achievement of the education index is lower than the health index and the expenditure index. Therefore, it is essential to improve the education index. This study aims to analyze the factors that influence the education index. This study uses secondary data in panel data, a combination of time-series data from 2014 to 2019, and cross-section data from 11 sub-districts. Panel data to measure the factors that affect the Education Index were analyzed using regression analysis. The results show that the teacher to student ratio at elementary school has a negative effect on the education index, the class to student ratio at elementary school has a positive effect on the education index, while the school to student ratio at elementary school, school to student ratio at junior high school, class to student ratio at junior high school and teacher to student ratio at junior high school do not affect the education index.